The Fund-amental$ - Cheong, Zhi Wei (Nanyang Technological University, 2024)
The Fund-amental$ is a communication campaign aimed at encouraging long-term investing among young adults aged 21-30 in Singapore. Given the rising cost of living, investing has emerged as a crucial means for securing financial stability in the future. Despite growing concerns over inflation and living expenses, recent data indicates that 40% of Singaporeans hold idle savings exceeding six months' worth of their salary, posing a risk of stagnant financial growth (Syfe, 2022). Furthermore, only 16% of individuals in their 20s are effectively planning for retirement (OCBC, 2023), potentially compromising their financial and emotional well-being. The campaign adopts a three-pronged strategy: Sow, Grow, and Reap, aimed at addressing these challenges. This entails (1) increasing awareness about the advantages and simplicity of Long-Term Investment (LTI), (2) shifting perceived descriptive norms towards LTI, and (3) improving the self-efficacy of our target audience, thereby boosting their confidence to embark on their LTI journeys. Drawing upon insights from the Integrated Model for Behavioral Prediction (IMBP) and our formative research, our objectives are centred around key constructs including knowledge, attitude and self-efficacy, to drive intention towards long-term investing behaviour. Execution involved disseminating informative content via Instagram, organising offline roadshows, and developing a one-stop website encompassing an investment personality quiz and credible investment resources. Over the course of the 17-week campaign, notable achievements were realised, including a 12.7% increase in perceived intention to initiate long-term investing and a 14.6% increase in self-efficacy among the target audience.